A REVIEW ON SOME HEAVY METALS TOXICITY ON HAEMATOLOGICAL PARAMETERS IN FRESH WATER FISHES - UMAMAGESHWARI, M.; RAJESWARI, S. UMA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Heavy metals contamination could be a significant subject within the aquatic ecosystem. The toxic levels of heavy metals are also of agricultural, industrial, and mining activities. This may cause pollution and changes within the physicochemical characteristics of the aquatic environment. This pollution has high toxicant effects on fishes, fish products as well as fish environment and human health. The Aim of this study was to detect the contamination levels and the health status of fishes, and study the effect of various heavy metals like Pb, Hg, Fe, Cr, Cu, and Zn etc. on several blood parameters like RBC, WBC, Hb, PCV, MCH, MCV, and MCHC. The obtained results the contamination of the aquatic systems with heavy metals from natural anthropogenic sources has become a worldwide problem which poses threats to ecosystems and natural communities. Hence, this study reviews the consequences of heavy metals in freshwater fishes. Fishes bioaccumulate heavy metals (including cadmium, zinc, lead, and copper) through various organs like gills, liver, stomach and intestine. The consequences of those heavy metals are highlight and compared with their permissible limit advised by the Food and Agriculture Organization (FAO) of the United Nations, 1983. For all the above reasons, this review aimed to check the contributed of such heavy metals within the environment, toxic mechanism, and toxic effects on fish.